PENGARUH PENGATURAN KUAT ARUS DAN VOLTASE TERHADAP KEKUATAN TARIK PADA PENGELASAN BIMETAL PLAT BAJA KARBON RENDAH DAN STAINLESS STEEL 304 DENGAN LAS GMAW - Sarjiyana .; Subagiyo Subagiyo; Lisa Agustriyana (Polinema Press, Politeknik Negeri Malang, 2021)
A manufactured product in the form of a mixture of dissimilar materials (bimetal) must be considered, including: selecting the right metal, selecting the appropriate filler, setting the current and voltage, etc. For this reason, research related to bimetallic welding using Gas Metal Arc Welding (GMAW) was conducted. The aims were to determine the effect of current on the tensile strength of bimetallic welding of low carbon steel and stainless steel 304 using GMAW welding, to determine the effect of voltage on the tensile strength of bimetallic welding, and to determine the effect of the interaction of current and voltage on the tensile strength of bimetallic welding using welding. GMAW. The research method used is experimental where the results of bimetallic welding are tested by the destructive test method. The results showed that current, voltage, and the strong interaction between current and voltage affect the tensile strength of bimetallic welding of low carbon steel and stainless steel 304 using GMAW welding. The use of amperes between 120A-160A and a voltage of 19V-22V gives a small difference and a tensile strength of 300 MPa-330 MPa.